STATUS PENYAKIT INFECTIOUS HYPODERMAL AND HAEMATOPOIETIC NECROSIS VIRUS (IHHNV) YANG MENGINFEKSI BUDIDAYA UDANG VANNAMEI (Litopenaeus vannamei) DI KABUPATEN PINRANG - Wahyu Widodo; Ilmiah Ilmiah; Siti Hadijah (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2022)
Infectious Hypodermal Haematopoietic Necrosis Virus (IHHNV) is one of the diseases that is the main cause of decreased production of vanamei shrimp. This study aims to: 1) detect IHHNV in vannamei shrimp using the Poymerase Chain Reaction (PCR) method; 2). Knowing the disease status of Infectous Hypodermal and Haematopoietic Necrosis Virus (IHHNV) Infecting Vannamei Shrimp Cultivation in Pinrang Regency; 3). IHHNV Virus Disease Control Strategy in Vannamei Shrimp Cultivation Activities. The research method used is a total of 252 samples taken from 14 ponds in two districts. The organs observed were swimming legs. The research stages include sample preparation and DNA extraction, DNA sample extraction using DTAB-CTAB. Furthermore, DNA amplification and detection of PCR products. To see the amplified PCR product, further analysis through electrophoresis is needed. The results showed that the swimming legs of the vannamei shrimp were not infected with the IHHNV virus. Based on the results of the PCR test using Primer KIT (IQ2000TM IHHNV Detection and Prevention System) showed that all samples of Vannamei Shrimp (Litopenaeus Vannamei) were not infected with the IHHNV Virus.